Implementation of a Family Support Grant to Subsidize Caregiving Needs and Support Attendance at American Society for Nutrition's Annual Professional Scientific Conference. Issue 6 (23rd June 2022) - Cardel, Michelle I; Loop, Matthew S; Brown, Andrew W; Bohan Brown, Michelle M; Newsome, Faith; Scott, Lorraine; Lemas, Dominick J; Krukowski, Rebecca A
ABSTRACT: Attendance at professional society meetings facilitates networking, collaboration, and success in academic/scientific fields. Insufficient funds, support, or resources for caregiving can inhibit attendance for parents/caretakers, who may become professionally disadvantaged by not attending professional society conferences. The American Society for Nutrition (ASN) offered a family support grant for caregiving needs during the annual conference (maximum: $750); however, the perceived impact of caregiving funds on attendance outcomes is unknown. The objective of this study was to assess the need of family support for attendance to the ASN annual conference among applicants and to assess recipients' experience and usage of funds. Applicants completed a pre-conference survey assessing requested funds, out-of-pocket caregiving expenses to attend the meeting, the influence of receiving the grant on attendance, and additional factors. Recipients completed a post-conference survey assessing use of the funds and impact of the grant on attending/participating. Grant applications ( n  = 110) were majority women, aged 26–45 y, married, at the trainee or assistant professor level, from diverse racial/ethnic backgrounds, and with parenting noted as the primary responsibility. Thirty-seven percent of applicants were currently lactating or expressing milk. The average amount requested was $650 US dollars, and >60% of respondents indicated plans to use funds to bring a family member/friend to the conference. Seventy-seven percent of respondents indicated that receiving the grant would influence their attendance. The post-conference survey ( n  = 25) indicated that recipients felt that receiving the grant was helpful in attending the conference (92%), specifically attending scientific sessions (96%) and poster sessions (80%). Recipients indicated the grant helped them network with attendees (88%), visit the exhibitor hall (72%), and participate in career development activities (64%). The ASN family support grant aided attendance and supported recipients' participation in conference activities, particularly early-career women who are parents, with the goal of supporting diversity and inclusivity in scientific/academic fields. This trial was registered at www.clinicaltrials.gov as NCT03432585. Abstract : This paper describes the impact of a family support grant on attendance and the utilization of resources at a conference held by a professional society in nutrition.